The Impact of Transformational Leadership on High School Students' Academic Performance at a Private School in Dubai - ALHAJJI, HUZAIFA (2024)
Although transformational leadership has immense potential to increase academic performance, its effectiveness within private high schools in Dubai's fast-growing educational scene has not been well investigated. This research intends to fill the void of knowledge by looking at how transformational leadership affects the academic performance of Dubai's private high school students. The research combined qualitative insights gained from interviews with quantitative data from professionally-written questionnaires using a mixed-methods approach. The research included a diverse sample, consisting of thirty teachers and ninety students. The study results demonstrate the significant role of transformational leadership in fostering an educational atmosphere that enhances student engagement and academic achievement. Quantitative studies have clearly shown a correlation between the use of transformational leadership practices and improvements in student success metrics. Thematically, the analysis reveals a shift in school culture towards a more encouraging, inventive, and cooperative environment, facilitated by transformative leaders who cultivate a powerful sense of unity and common goals among students and staff. The practical ramifications of this research are significant, providing practical insights for school administrators, educators, and legislators who are working to improve educational methods. Using transformational leadership techniques may help to improve teaching and learning opportunities, particularly in competitive academic settingsuch as those found in Dubai that draw on diversity. These results should be considered by stakeholders involved in creating policies and leadership development initiatives that give emotional intelligence and inspirational ability top priority. This will help them to more effectively address the difficulties posed by contemporary educational expectations.